Estudo “in vitro” e “in vivo” da administração subaracnóide de opióides hiperbáricos em cavalos - Polydoro, Alexandre da Silva (2006)
This study reports the investigation of hyperbaric opioids and 10% glucose studied in a experimental in vitro model of a subarachnoid space and the in vivo subarachnoid administration of hyperbaric opioids and 10% glucose in horses. The first in vitro phase was done with a translucid poly vinil chloride (PVC) model filled with horse cerebral spinal fluid and injected with hyperbaric opioids and 10% glucose tinted with methylene blue. The objective was to evaluate the physic behavior of the substances within the model. In the second in vivo phase, the hyperbaric opioids (morphine, methadone and buprenorphine) were subarachnoidally administered in six adult horses through a subarachnoid catheter. Cardiopulmonary effects, behavior and pain threshold to noxious electrical stimulation on the perineal, lumbar, sacral and thoracic dermatomes was evaluated. Theresults demonstrated that the model was able to indicate the more appropriate opioids to be used subarachnoidally, and that segmental analgesia was considered intense with hyperbaric morphine and hyperbaric methadone, and moderate with hyperbaric buprenorphine, with minimal effects on cardiorespiratory function, without ataxia or CNS excitation.